Intraspecific variation in soy across the leaf economics spectrum. (9th August 2018) - Hayes, Fallon J; Buchanan, Serra W; Coleman, Brent; Gordon, Andrew M; Reich, Peter B; Thevathasan, Naresh V; Wright, Ian J; Martin, Adam R
Abstract: Background and Aims: Intraspecific trait variation (ITV) is an important dimension of plant ecological diversity, particularly in agroecosystems, where phenotypic ITV (within crop genotypes) is an important correlate of key agroecosystem processes including yield. There are few studies that have evaluated whether plants of the same genotype vary along well-defined axes of biological variation, such as the leaf economics spectrum (LES). There is even less information disentangling environmental and ontogenetic determinants of crop ITV along an intraspecific LES, and whether or not a plant's position along an intraspecific LES is correlated with reproductive output. Methods: We sought to capture the extent of phenotypic ITV within a single cultivar of soy ( Glycine max ) – the world's most commonly cultivated legume – using a data set of nine leaf traits measured on 402 leaves, sampled from 134 plants in both agroforestry and monoculture management systems, across three distinct whole-plant ontogenetic stages (while holding leaf age and canopy position stable). Key Results: Leaf traits covaried strongly along an intraspecific LES, in patterns that were largely statistically indistinguishable from the 'universal LES' observed across non-domesticated plants. Whole-plant ontogenetic stage explained the highest proportion of phenotypic ITV in LES traits, with plants progressively expressing more 'resource-conservative' LES syndromes throughout development. Within ontogenetic stages, leaf traits differed systematically across management systems, with plants growing in monoculture expressing more 'resource-conservative' trait syndromes: trends largely owing to an approximately ≥50% increases in leaf mass per area (LMA) in high-light monoculture vs. shaded agroforestry systems. Certain traits, particularly LMA, leaf area and maximum photosynthetic rates, correlated closely with plant-level reproductive output. Conclusions: Phenotypic ITV in soy is governed by constraints in trait trade-offs along an intraspecific LES, which in turn (1) underpins plant responses to managed environmental gradients, and (2) reflects shifts in plant functional biology and resource allocation that occur throughout whole-plant ontogeny.